(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
Students graduate from accredited programs every year with skills and competencies required by their profession of choice. However, employability remains an issue after graduation. Industry leaders and educators have a statistically significant difference in graduate preparedness for the workforce. When attempting to find a position in their career, graduates are told that without experience, they cannot secure a job. How does one attain the experience desired by employers? This paper posits that university connections and partnerships will assist graduates in securing positions and other required skills after graduation. The purpose of this paper is to extend the work started by Jackson, Lower, and Rudman, using an evidence-based management approach, to synthesize frameworks that will support allied health education programs with bridging the gap between curriculum, internships, practicums, and graduate employability. Also discussed will be the importance of considering both hard and soft skills in graduate employability.